Identification and distribution of lactic acid bacteria during the ripening of şavak tulum cheese - Öksüztepe, Gülsüm; Patir, Bahri; Çalicio?lu, Mehmet (My University, 2005)
This study was undertaken to determine changes in the flora of lactic acid bacteria during the ripening of Şavak tulum cheese and to identify the major species playing an important role in the ripening process. Tulum cheese was produced from raw sheep milk using traditional methods and ripened in plastic containers at 4°C for 90 days. Samples were taken on days 0, 15, 30, 60 and 90 and analyzed for isolation and identification of lactic acid bacteria. A total of 783 isolates of lactic acid bacteria were identified. The results indicated that, in general, lactic streptococci were predominant within the first month of ripening and, then, replaced by lactobacilli. It is concluded that Lactobacillus casei subsp. casei, Lactobacillus plantarum from the family Lactobacillaceae and Lactococcus lactis subsp. cremoris, Lactococcus lactis subsp. lactis, and Leuconostoc mesenteroides subsp. cremoris from the family Streptococcaceae were the predominant species among the isolates, indicating that these species may play a major role in the ripening of tulum cheese. © TÜBİTAK.
Keywords: Lactic acid bacteria; Ripening; Tulum cheese